An Approach for Instantaneous Ambiguity Resolution for Medium- to Long-range Multiple Reference Station Networks - Hu, Guorong; Abbey, Donald; Castleden, James; Featherstone, Will; Ovstedal, O (John Wiley and Sons, Inc., 2004)
Integer ambiguity resolution (AR) is a prerequisite for all high-precision (centimetre level) GPS applications that utilise multiple reference station (MRS) networks. However, due to the presence of distance-dependent GPS errors, notably atmospheric refraction, AR across the network is difficult on an epoch-by-epoch basis, especially for medium- to long-range (typically 30?130 km as used here) MRS networks. This paper presents an approach for medium- to long-range instantaneous AR for MRS networks, based on an ionosphere-weighted observation model and network geometry constraints, along with a multiple ambiguity validation test procedure. The performance of the proposed method was demonstrated through two case-study examples from Australia and Norway. Our test results show that the instantaneous AR success rate varied from 93% (131 km baseline) to 98% (35 km baseline).It is also shown that the adopted high-precision prediction models for the double-difference (DD) ionospheric delay and residual tropospheric zenith delay (RTZD) are of benefit to the high success rate of the network AR. Due to its epoch-by-epoch nature, the proposed approach is insensitive to cycle-slips, rising or setting satellites, or loss-of-lock.